Influence of programme of study on the adjustment challenges faced by Colleges of Education Students in Eastern region, Ghana - Kumah, Gabriel; Doh-Fia, Stephen; Kwarteng-Nantwi, Eugene; Omotosho, Joshua A. (Ghana Journal of Education: Issues and Practice (GJE), 2022)
The purpose of the study was to explore the influence of the programme of study on the adjustment challenges faced by colleges of education students in the Eastern Region of Ghana. Using the descriptive research survey design, data were collected from 320 students through an online questionnaire. The Validity of the research instrument was ascertained through a pilot study carried out at Foso College of Education. The reliability coefficient for the questionnaire, estimated through Cronbach’s alpha coefficient, was 0.872. The collected data were analysed using ANOVA. The study found that the programme of study had a significant influence on the adjustment challenges faced by colleges of education students in Eastern Region of Ghana. The B.Ed. JHS programme respondents’ adjustment challenges differed significantly from those of the other two programmes (B.Ed. Primary and B.Ed. Early Childhood). The researchers suggested that college counsellors/administrators assess the frequency and intensity of adjustment problems among students, JHS major students especially, so as to assist relevant bodies at colleges of education in Eastern Region in designing appropriate orientation programmes and peer mentoring programmes.